How to create a MWE lexical entry - Petrovski, Aleksandar; Zdravkova, Katerina (My University, 2014)
One suggestion how to create a MWE lexical entry is given. Although NooJ syntax has been used, it is applicable to any other NLP system. Classification adopted by Parseme action has been used when defining codes of MWE properties. Problems with lexicalising flexible MWEs are discussed.